2018
DOI: 10.1016/j.crci.2018.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Removal of fluoride from groundwater using natural clay (kaolinite): Optimization of adsorption conditions

Abstract: This article focuses on the application of clay, kaolinite, for the removal of fluoride ion from Saharan groundwater located in the Tindouf region (Algeria) because high concentrations are detected in potable water. Adsorption tests show that fluoride ion removal was efficient when the pH varies from 4.5 to 6. Under these conditions, the adsorption capacities were 0.442 and 0.448 mg/g, respectively. Kinetic and isotherm adsorption correlations were applied to describe the adsorption process. The results showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(28 citation statements)
references
References 33 publications
3
20
0
Order By: Relevance
“…e electrostatic interaction between the positively charged MB and H + weakens the adsorption process. Conversely, occurrence of deprotonation of the tea stem powder increases the number of active adsorption sites and reduces electrostatic force [29,50,51]. erefore, the effect of pH on the adsorption of MB in this study reveals that the removal efficiency maintains constantly at the pH range of 5.0-11.0, which agrees with the pH zpc of tea stem powder.…”
Section: Effect Of Phsupporting
confidence: 77%
“…e electrostatic interaction between the positively charged MB and H + weakens the adsorption process. Conversely, occurrence of deprotonation of the tea stem powder increases the number of active adsorption sites and reduces electrostatic force [29,50,51]. erefore, the effect of pH on the adsorption of MB in this study reveals that the removal efficiency maintains constantly at the pH range of 5.0-11.0, which agrees with the pH zpc of tea stem powder.…”
Section: Effect Of Phsupporting
confidence: 77%
“…A comparison with other adsorbents indicated a high metal ion adsorption capacity of nano platelets kaolinite. Present study results are in line with previous studies (Abukhadra et al, 2019;Amer and Awwad, 2018;Chen et al, 2019;Fatimah, 2018;He et al, 2019;Kuang et al, 2019;Ma et al, 2019;Nabbou et al, 2019;Ruyter-Hooley et al, 2017;Zhu et al, 2018) that kaolinite could be a potential adsorbent for the pollutants of environmental concern.…”
Section: Comparison Of Platelets Nano Kaolinite With Other Kaolin Adssupporting
confidence: 93%
“…Adsorption experiments show effective fluoride ion removal when the pH ranges between 4.5 and 6. The adsorption capacities under these conditions were 0.442 and 0.448 mg/g, respectively (Nabbou et al, 2019). The authors suggested that natural clay comprised of SiO 2 (53.83%) and Al 2 O 3 (39.81%) could be an excellent adsorbent for removal of fluoride from groundwater in Tindouf (Algeria), where fluoride concentrations often exceed recommended drinking water standards.…”
Section: Fluoride In Groundwatermentioning
confidence: 99%